2022
DOI: 10.3892/etm.2022.11221
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for the safety and efficacy of retrograde laser lithotripsy: Data from a contemporary series of 155 consecutive patients with single and multiple lithiasis of the urinary tract

Abstract: Treatment of large and multiple stones located in the ureter and/or the kidney may be challenging. The aim of the current study was to evaluate the results and complications of retrograde endoscopic lithotripsy for stones located in the urinary tract and to determine prognostic factors for treatment outcome. From April 2017 to March 2020, eligible patients for the active treatment of ureterolithiasis with or without concomitant nephrolithiasis <20 mm were enrolled in the study. The prognostic factors for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
3
2
0
Order By: Relevance
“…Our study found that the operative time in the multiple stones group was significantly longer than that in the solitary stone group, which seems logical: more stones obviously require more time. DIOMIDIS et al showed that the operative time for RIRS was 57.5 min (42 min–90 min) for solitary stone and 88 min (55 min–105 min) for multiple stones, which is consistent with our study ( 16 ). However, in their study, semi-rigid ureteroscopy was used to treat solitary calculi, which were all ureteral calculi.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study found that the operative time in the multiple stones group was significantly longer than that in the solitary stone group, which seems logical: more stones obviously require more time. DIOMIDIS et al showed that the operative time for RIRS was 57.5 min (42 min–90 min) for solitary stone and 88 min (55 min–105 min) for multiple stones, which is consistent with our study ( 16 ). However, in their study, semi-rigid ureteroscopy was used to treat solitary calculi, which were all ureteral calculi.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, it was concluded that stone length was an independent risk factor for SFR rather than stone number and location (16), which is similar to our findings. There was no significant difference in SFR between the single stone group and the multiple stone group in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared with the younger population, older patients appeared to be more vulnerable. The aging urinary tract system as well as an increased volume of the prostate in male patients may contribute to the development of lower urinary tract symptomatology, infections, and fever in older patients following surgery[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many studies on the prognostic factors of stone removal surgery. Kozyrakis D et al found that neither the number nor location of stones had a significant effect on the outcome of lithotripsy (19), so physicians should not discourage the use of f-URS in patients with multiple kidney stones. Studies showing that the number of stones affects the outcome of surgery are mostly focusing on SWL (20).…”
Section: Discussionmentioning
confidence: 99%